2022
DOI: 10.1007/s00412-022-00778-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Sp1 regulates mitotic chromosome assembly and segregation

Abstract: Aneuploidy is a pervasive feature of cancer cells that results from chromosome missegregation. Several transcription factors have been associated with aneuploidy; however, no studies to date have demonstrated that mammalian transcription factors directly regulate chromosome segregation during mitosis. Here, we demonstrate that the ubiquitously expressed transcription factor specificity protein 1 (Sp1), which we have previously linked to aneuploidy, has a mitosis-specific role regulating chromosome segregation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Sp1, a ubiquitously expressed mammalian transcription factor, plays a pivotal role in maintaining genome integrity through diverse mechanisms [ 58 , 59 ]. Recent research has revealed that Sp1 is essential for the assembly of mitotic chromosomes, thereby facilitating cell proliferation [ 60 ]. In vivo studies on YY1 knockout mice derived from skeletal muscle satellite cells have demonstrated that inducible deletion of YY1 significantly impedes the process of muscle repair caused by acute damage and exacerbates the dystrophic phenotype resulting from chronic injury [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sp1, a ubiquitously expressed mammalian transcription factor, plays a pivotal role in maintaining genome integrity through diverse mechanisms [ 58 , 59 ]. Recent research has revealed that Sp1 is essential for the assembly of mitotic chromosomes, thereby facilitating cell proliferation [ 60 ]. In vivo studies on YY1 knockout mice derived from skeletal muscle satellite cells have demonstrated that inducible deletion of YY1 significantly impedes the process of muscle repair caused by acute damage and exacerbates the dystrophic phenotype resulting from chronic injury [ 61 ].…”
Section: Discussionmentioning
confidence: 99%